Tandem catalyst for preparing high-carbon hydrocarbon through CO2 hydrogenation as well as preparation method and application of tandem catalyst

Through the tandem catalyst system, using Na/Fe4N and Pd@MCM-41 catalysts, the problems of low CO2 conversion and high reaction conditions of high carbon hydrocarbon catalysts in the prior art are solved, and high efficiency high carbon hydrocarbons are achieved The generation and catalyst stability have been improved, and CO2 exhaust gas has been successfully converted into high-carbon hydrocarbon energy.

CN119236992APending Publication Date: 2025-01-03ZHENGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411326885.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing high-carbon hydrocarbon catalysts for hydrogenation of CO2 have problems with low CO2 conversion and high-temperature reaction conditions, and lack multifunctional catalysts with high activity, high selectivity and high stability.

Method used

A tandem catalyst system is adopted, including the upper Na/Fe4N catalyst and the lower Pd@MCM-41 molecular sieve catalyst, to form a low-carbon olefin intermediate through CO2-FTS reaction, and olefins are linearly polymerized on the surface of the lower catalyst to form high-carbon hydrocarbons.

Benefits of technology

High CO2 conversion rate and high carbon hydrocarbon selectivity are achieved, while improving the stability of the catalyst, and successfully converting CO2 exhaust gas into high carbon hydrocarbon energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236992A_ABST
    Figure CN119236992A_ABST
Patent Text Reader

Abstract

The invention provides a tandem catalyst for preparing high-carbon hydrocarbon through CO2 hydrogenation as well as a preparation method and application of the tandem catalyst. The preparation method comprises the following steps: preparing a Na / Fe4N catalyst which is filled in the upper layer of a reactor and is used for preparing low-carbon olefin through CO2 hydrogenation; the molecular sieve catalyst is filled in the lower layer of the reactor and is used for low-carbon olefin oligomerization, the molecular sieve catalyst is Pd-coated MCM-41 and is formed by embedding noble metal Pd in MCM-41 molecular sieve pore channels, the loading capacity of Pd is 0.5 wt%-3wt%, and the mass ratio of Na / Fe4N to MCM-41 is 1: 4-4: 1. According to the invention, higher high-carbon hydrocarbon selectivity can be obtained while high CO2 conversion rate can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and more specifically, to a series catalyst for producing higher carbon hydrocarbons by hydrogenation of CO2, and a preparation method and application thereof. Background Art

[0002] With the development and utilization of non-renewable resources such as coal, oil, and natural gas, the content of carbon dioxide in the atmosphere has increased sharply. Faced with the increasingly severe pressure of CO2 emission reduction and the huge carbon emission trading market, how to efficiently utilize CO2 resources is a hot topic in C1 chemistry research. In order to cope with the challenges brought by global climate change and environmental pollution and achieve sustainable development, converting CO2 into high value-added products such as formic acid, methanol, high carbon hydrocarbons, and aromatics is an effective measure to reduce CO2. Therefore, research and development of the production of high carbon hydrocarbons using CO2 as raw materials is extremely in line with the country's energy strategy needs.

[0003] At present, the reaction pathways for the hydrogenation of CO2 to produce olefins are mainly divided into the Fischer-Tropsch synthesis route (FTS) and the methanol-to-olefins route (MTO). In the Fischer-Tropsch synthesis route, CO2 is first reduced by the reverse water gas shift reaction (RWGS) to form a CO intermediate, and CO is then hydrogenated by the Fischer-Tropsch synthesis to form olefins. Fe-based catalysts are widely studied because of their low price and their simultaneous reverse water gas and Fischer-Tropsch activity. In addition, the reaction conditions of Fe-based catalysts are relatively mild (300-350°C), and the CO2 conversion rate is high, but they are limited by the FTS product distribution law (ASF). For the methanol-to-olefins route, CO2 and H2 are first converted into methanol intermediates through CO or formate on the surface of partially reduced metal oxides (such as Cu, In, Al and Zn) or precious metals, and the methanol intermediates are dehydrated to produce olefins under the action of acidic molecular sieves. However, the reaction temperature is relatively high (360-400°C), the CO2 conversion rate is low, and the by-product CO selectivity is high (>35%). It can be seen that whether it is the Fischer-Tropsch synthesis route or the methanol-to-olefins route, the current catalysts have shortcomings, and there is an urgent need to develop multifunctional catalysts with high activity, high selectivity, high stability and mild reaction conditions for CO2 hydrogenation to produce higher carbon hydrocarbons. Summary of the invention

[0004] One of the purposes of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a series catalytic system for preparing higher carbon hydrocarbons by hydrogenation of CO2, so as to ensure a high CO2 conversion rate while obtaining a higher selectivity for higher carbon hydrocarbons.

[0005] One aspect of the present invention provides a method for preparing a tandem catalyst for producing high-carbon hydrocarbons by hydrogenating CO2, the preparation method comprising: preparing a Na / Fe4N catalyst for preparing low-carbon olefins by hydrogenating CO2 loaded in an upper layer of a reactor; and preparing a molecular sieve catalyst for low-carbon olefin polymerization loaded in a lower layer of the reactor, wherein the molecular sieve catalyst is Pd@MCM-41, which is composed of precious metal Pd embedded in the pores of the MCM-41 molecular sieve, wherein the loading amount of Pd is 0.5wt% to 3wt%, and the mass ratio of Na / Fe4N to MCM-41 is 1:4 to 4:1.

[0006] In an exemplary embodiment, the preparation of a Na / Fe4N catalyst for preparing light olefins by hydrogenating CO2 loaded on the upper layer of a reactor may include the following steps: S101, adding a metal iron salt to an aqueous solution to form a mixed salt solution, stirring and gradually cooling the temperature to 10°C to 30°C, maintaining the constant temperature for 1 to 2 days, and while maintaining the same temperature, dripping an ammonium carbonate solution into the mixed salt solution to form a final precipitation system, wherein the concentration of the metal salt solution is 0.1 to 1.0 mol / L, and the molar amount of ammonium carbonate in the dripped ammonium carbonate solution is the mixed salt solution. 1 to 5 times the molar amount of the metal salt in the salt solution; S102, stirring the final precipitation system for 1 to 10 hours, taking out the precipitate, filtering it, washing it with excess deionized water, drying it and calcining it; S103, impregnating the obtained calcined material with 1 to 10 mL of sodium nitrate solution, wherein the molar amount of sodium nitrate in the sodium nitrate solution is 0.05 to 0.1 times that of the iron salt; S104, stirring the mixture obtained in step S103 at 80 to 100°C, evaporating it to dryness and then drying it; S105, roasting the product obtained in step S104 under NH3 atmosphere.

[0007] In an exemplary embodiment, the iron salt is a divalent or trivalent metal salt soluble in water, and the iron salt is one of ferrous chloride, ferrous chloride, ferrous nitrate, and ferric nitrate.

[0008] In an exemplary embodiment, the dropping speed of the ammonium carbonate solution may be 1 to 5 mL / min.

[0009] In an exemplary embodiment, the temperature range of drying the precipitate in S102 may be 80-100°C.

[0010] In an exemplary embodiment, the calcination temperature in the NH3 atmosphere in step S105 may be in the range of 500 to 700°C, and the calcination time may be 3 to 5 hours.

[0011] In an exemplary embodiment, the preparation of the molecular sieve catalyst loaded in the lower layer of the reactor for the polymerization of light olefins may include the following steps: S201, dissolving the template in deionized water, stirring and dissolving to obtain a clear solution, wherein the template is one or a combination of two or more of hexadecyltrimethylammonium bromide, tetrapropylammonium bromide, n-butylamine, tetraethylammonium hydroxide, tetramethylammonium hydroxide, and tripropylamine; S202, dropping a mixed solution of silicon source and aluminum source into the solution in S201 and stirring thoroughly; S203, dissolving a palladium precursor in a small amount of solvent and dropping it into S202 and stirring thoroughly; S204, dropping an alkali solution into S203, adjusting the pH value, and obtaining an emulsion; S205, adding the emulsion in S204 to a polytetrafluoroethylene liner to perform a hydrothermal reaction; S206, centrifuging and washing the mixture after the hydrothermal reaction until it is neutral, drying, and then calcining in a muffle furnace to remove the template.

[0012] In an exemplary embodiment, the mass concentration of the template may be 3% to 7%.

[0013] In an exemplary embodiment, the silicon source may be one or a combination of two or more of ethyl orthosilicate, silicic acid and sodium silicate.

[0014] In an exemplary embodiment, the aluminum source may be one or a combination of two or more of sodium aluminate, aluminum sulfate, boehmite, metallic aluminum, aluminum nitrate, aluminum isopropoxide, and aluminum hydroxide.

[0015] In an exemplary embodiment, the palladium salt may be one or a combination of two or more of palladium nitrate, palladium chloride and palladium sulfate.

[0016] In an exemplary embodiment, the solvent may be one or a combination of two or more of water, methanol and ethanol.

[0017] In an exemplary embodiment, the alkali solution may be one of ammonia water, sodium hydroxide and sodium carbonate, and the adjusted pH value is between 8 and 11.

[0018] In an exemplary embodiment, the molar ratio of the silicon source, the aluminum source, the template, the alkali solution and the water in the mixed solution may be 1: (0.02-0.05): (0.2-0.3): (4-8): (100-120).

[0019] In an exemplary embodiment, the hydrothermal temperature may be 1 to 180° C., and the hydrothermal time may be 50 to 100 hours.

[0020] In an exemplary embodiment, the drying temperature may be 80 to 120° C., and the drying time may be 4 to 48 hours.

[0021] In an exemplary embodiment, the calcination temperature may be 400-700° C., the heating rate may be 0.5-5° C. / min, and the calcination time may be 8-10 h.

[0022] In an exemplary embodiment, the particle size of the Na / Fe4N catalyst and the molecular sieve catalyst may be 80-120 mesh.

[0023] According to another aspect of the present invention, a series catalyst for producing higher carbon hydrocarbons by hydrogenation of CO2 is provided. The series catalyst for producing higher carbon hydrocarbons by hydrogenation of CO2 is obtained by the preparation method described above.

[0024] According to another aspect of the present invention, a method for preparing high carbon hydrocarbons by hydrogenating CO2 is provided, characterized in that the preparation method uses a series catalyst obtained by the preparation method as described above to prepare high carbon hydrocarbons, and the preparation method may include: at a reaction temperature of 200-400°C and a reaction pressure of 1.0-3.0 MPa, using a mixed gas with a molar ratio of CO2:H2=1:(0.5-5) and a space velocity GHSV of 5000h -1 ~5000h -1 , react for 50 to 300 hours, collect C at the reactor outlet 5+ Olefin products; and a CO2:H2 / Ar mixed gas of CO2:H2=1:(1.0-5.0), wherein the volume fraction of Ar in the mixed gas is 30%-60%.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention realizes the directional synthesis of low-carbon olefins from CO2 and the polymerization of low-carbon olefins into high-carbon hydrocarbons in series, thereby achieving a high CO2 conversion rate and a relatively high generation of high-carbon hydrocarbon products.

[0027] (2) The catalyst responsible for the polymerization of low-carbon olefins in the lower layer of the present invention has a special structure, and the Pd particles are encapsulated inside the pores of MCM-41, which greatly improves the stability of the catalyst.

[0028] (3) The present invention successfully utilizes CO2 waste gas that has an impact on the climate environment and converts it into high-carbon hydrocarbon energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings illustrate exemplary embodiments of the inventive concept and, together with the description, serve to explain the principles of the inventive concept. The accompanying drawings are included to provide a further understanding of the inventive concept and are incorporated in and constitute a part of this specification.

[0030] Figure 1The XRD diagram of Na / Fe4N prepared by the tandem catalyst and preparation method for CO2 hydrogenation to produce high carbon hydrocarbons according to an exemplary embodiment of the present invention;

[0031] Figure 2 The XRD diagram of Pd@MCM-41 prepared by the tandem catalyst and preparation method for CO2 hydrogenation to produce high carbon hydrocarbons according to an exemplary embodiment of the present invention;

[0032] Figure 3 The stability test results of the catalyst sample (Na / Fe4N+Pd@MCM-41) prepared by the tandem catalyst and preparation method for CO2 hydrogenation to produce higher carbon hydrocarbons according to an exemplary embodiment of the present invention. DETAILED DESCRIPTION

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] As mentioned above, the first aspect of the present invention provides a method for preparing a tandem catalyst for hydrogenating CO2 to produce high-carbon hydrocarbons, the preparation method comprising: S1 preparing a Na / Fe4N catalyst for preparing low-carbon olefins by hydrogenating CO2 loaded in the upper layer of the reactor; and S2 preparing a molecular sieve catalyst for low-carbon olefin polymerization loaded in the lower layer of the reactor, the molecular sieve catalyst is Pd@MCM-41, which is composed of precious metal Pd embedded in the pores of MCM-41 molecular sieve, wherein the loading amount of Pd is 0.5 to 3 wt%. Here, the precious metal Pd has high activity but is expensive, and only 0.5 to 3 wt% is required to achieve the target activity, and the mass ratio of Na / Fe4N to MCM-41 is 1:4 to 4:1.

[0035] The tandem catalytic system is composed of a Na / Fe4N catalyst for preparing light olefins by hydrogenating CO2 loaded on the upper layer of the reactor and a molecular sieve catalyst for light olefin polymerization loaded on the lower layer of the reactor, wherein the catalyst is composed of precious metal Pd embedded in the pores of MCM-41 molecular sieve, wherein the loading amount of Pd is 0.5-3wt%. The mass ratio of Na / Fe4N to MCM-41 is 1:4-4:1, CO2 is firstly efficiently and directionally synthesized into light olefin intermediates on the upper layer Na / Fe4N catalyst through CO2-FTS reaction, and the generated light olefin intermediates (ethylene, propylene, butene) are polymerized on the surface of the lower layer Pd / molecular sieve catalyst through the Cossee-Alman mechanism to prepare high carbon hydrocarbons, and the iron-based catalyst Na / Fe4N and Pd / molecular sieve are constructed into a composite catalyst, which is expected to make the ethylene, propylene, and butene generated in the iron-based center undergo olefin linear polymerization reaction at the Pd active center, so as to ensure a high CO2 conversion rate while obtaining a higher high carbon hydrocarbon selectivity.

[0036] S1 Preparation of Na / Fe4N catalyst for preparing light olefins by hydrogenation of CO2 loaded in the upper layer of the reactor may include the following steps:

[0037] S101, adding a metallic iron salt to an aqueous solution to form a mixed salt solution, stirring and gradually cooling to 25°C, maintaining a constant temperature for 1 day, and dripping an ammonium carbonate solution into the mixed salt solution while maintaining the same temperature to form a final precipitation system, wherein the concentration of the metal salt solution is 0.1-1.0 mol / L, and the molar amount of ammonium carbonate in the dripped ammonium carbonate solution is 1-5 times the molar amount of the metal salt in the mixed salt solution; S102, stirring the final precipitation system for 5 hours, taking out the precipitate, filtering it, washing it with excess deionized water, drying it, and calcining it; S103, impregnating the obtained calcined product with 1-10 mL (for example, 5 mL) of sodium nitrate solution, wherein the molar amount of sodium nitrate in the sodium nitrate solution is 0.05-0.1 times that of the iron salt; S104, stirring the mixture obtained in step S103 at 80-100°C, evaporating it to dryness, and drying it; S105, roasting the product obtained in step S104 under NH3 atmosphere.

[0038] The iron salt may be a divalent or trivalent metal salt soluble in water, and the iron salt may be one of ferrous chloride, ferrous chloride, ferrous nitrate, and ferric nitrate.

[0039] The dropping speed of the ammonium carbonate solution can be 1 to 5 mL / min.

[0040] The temperature range of the precipitate drying in S102 may be 80-100°C.

[0041] The calcination temperature in the NH3 atmosphere in step S105 may be in the range of 500 to 700°C, and the calcination time may be 3 to 5 hours.

[0042] S2 Preparation of a molecular sieve catalyst for low-carbon olefin polymerization loaded in the lower layer of a reactor may include the following steps: S201, dissolving a template in deionized water, stirring and dissolving to obtain a clear solution, wherein the template is one or a combination of two or more of hexadecyltrimethylammonium bromide, tetrapropylammonium bromide, n-butylamine, tetraethylammonium hydroxide, tetramethylammonium hydroxide, and tripropylamine; S202, dropping a mixed solution of a silicon source and an aluminum source into the solution in S201, and stirring thoroughly; S203, dissolving a palladium precursor in a small amount of solvent and dropping it into S202, and stirring thoroughly; S204, dropping an alkali solution into S203, adjusting the pH value, and obtaining an emulsion; S205, adding the emulsion in S204 to a polytetrafluoroethylene lining to perform a hydrothermal reaction; S206, centrifugally washing the mixture after the hydrothermal reaction until it is neutral, drying, and then calcining it in a muffle furnace to remove the template.

[0043] The template agent is preferably one or both of hexadecyltrimethylammonium bromide and tetraethylammonium hydroxide. The mass concentration of the template agent can be 3% to 7%, and can be preferably 5%.

[0044] The silicon source may be one or a combination of two or more of tetraethyl orthosilicate, silicic acid and sodium silicate, preferably tetraethyl orthosilicate.

[0045] The aluminum source may be one or a combination of two or more of sodium aluminate, aluminum sulfate, boehmite, metallic aluminum, aluminum nitrate, aluminum isopropoxide, and aluminum hydroxide, preferably aluminum isopropoxide.

[0046] The palladium salt may be one or a combination of two or more of palladium nitrate, palladium chloride and palladium sulfate.

[0047] The solvent may be one of water, methanol and ethanol, or a combination of two or more thereof.

[0048] The alkali solution may be one of ammonia water, sodium hydroxide and sodium carbonate, and the adjusted pH value may be between 8 and 11, preferably 10.

[0049] The molar ratio of the silicon source, the aluminum source, the template, the alkali solution and the water in the mixed solution can be 1: (0.02-0.05): (0.2-0.3): (4-8): (100-120).

[0050] The hydrothermal temperature can be 1-180°C, and the hydrothermal time can be 50-100 hours. Increasing the hydrothermal temperature or extending the hydrothermal time will affect crystallization. Preferably, the hydrothermal temperature is 130-170°C, and the hydrothermal time is 12-48 hours.

[0051] The drying temperature may be 80 to 120° C., and the drying time may be 4 to 48 hours. The drying temperature is preferably 100 to 110° C., and the drying time may be preferably 12 to 24 hours.

[0052] The calcination temperature may be 400-700° C., the heating rate may be 0.5-5° C. / min, and the calcination time may be 8-10 h.

[0053] The particle size of the Na / Fe4N catalyst and the molecular sieve catalyst may be 80-120 meshes.

[0054] According to another aspect of the present invention, a series catalyst for producing higher carbon hydrocarbons by hydrogenation of CO2 is provided. The series catalyst for producing higher carbon hydrocarbons by hydrogenation of CO2 is obtained by the preparation method described above.

[0055] According to another aspect of the present invention, a method for preparing high-carbon hydrocarbons by hydrogenating CO2 is provided, wherein the preparation method uses a series catalyst obtained by the preparation method as described above to prepare high-carbon hydrocarbons, and the preparation method comprises: at a reaction temperature of 200 to 400°C and a reaction pressure of 1.0 to 3.0 MPa, using a mixed gas with a molar ratio of CO2:H2=1:(0.5 to 5) and a space velocity GHSV of 5000 h -1 ~5000h -1 , react for 50 to 300 hours, collect C at the reactor outlet 5+ Olefin products; and a CO2:H2 / Ar mixed gas of CO2:H2=1:(1.0-5.0), wherein the volume fraction of Ar in the mixed gas is 30%-60%.

[0056] In order to better understand the above exemplary embodiments of the present invention, they are further described below with reference to specific examples.

[0057] Example 1

[0058] Preparation of Na / Fe4N catalyst

[0059] Take 10.41g of ferric nitrate and dissolve it in 200mL of deionized water to obtain solution A. Take another 23.21g of ammonium carbonate and dissolve it in 500mL of deionized water to obtain solution B. Add solution B at a rate of 1mL / min until the pH of the solution reaches 10. Continue stirring for 2h and then age it for 10h. The precipitate was washed with 3000mL of deionized water and dried at 80°C overnight. Grind the dried precipitate and calcine it in a muffle furnace. Heat it to 500°C at a heating rate of 2°C / min and keep it for 5h to obtain Fe2O3 catalyst. Take 0.641g of sodium nitrate and dissolve it in 5mL of deionized water to obtain solution C. Disperse the obtained Fe2O3 catalyst in solution C, stir and dry it in a 70°C water bath, and heat the dried product to 500°C at a heating rate of 2°C / min in an NH3 atmosphere and calcine it for 5h to obtain fresh Na / Fe4N. The XRD of Na / Fe4N catalyst is as follows Figure 1 shown.

[0060] Preparation of Pd@MCM-41 catalyst

[0061] Take 2.91g of hexadecyltrimethylammonium bromide and dissolve it in 43mL of water, and mark this solution as solution A. Then, drop 6.65mL of tetraethyl orthosilicate and 0.27mL of aluminum isopropoxide into solution A, and mark this solution as solution B. Dissolve 0.06g of palladium nitrate dihydrate in 5mL of deionized water, and mark this solution as solution C. Drop solution C into solution B, stir evenly to obtain solution D. Then, add 13.6mL of ammonia solution with a mass percentage concentration of 75% dropwise into solution D under stirring, and then stir the mixture at room temperature until a uniform emulsion is formed. The above emulsion is loaded into a hydrothermal reactor, heated to 130°C for reaction for 36h, and then taken out and naturally cooled to room temperature. The mixture after the hydrothermal reaction was then centrifuged and washed to neutrality. After drying in a drying oven at 100°C for 12 h, it was calcined in a muffle furnace, and the temperature was raised to 550°C at 1°C / min. After calcination for 6 h, 0.5 wt% Pd@MCM-41 was obtained. The XRD pattern of the Pd@MCM-41 catalyst is shown in FIG. Figure 2 as shown in .

[0062] Example 2

[0063] Preparation of Na / Fe4N catalyst

[0064] Take 20.82g of ferric nitrate and dissolve it in 200mL of deionized water to obtain solution A, take another 46.42g of ammonium carbonate and dissolve it in 500mL of deionized water to obtain solution B, add solution B at a rate of 5mL / min until the pH of the solution reaches 10, continue stirring for 2h and then place it for aging for 10h. The precipitate is washed with 3000mL of deionized water and dried at 100℃ overnight. Grind the dried precipitate and put it in a muffle furnace for calcination, heat it to 700℃ at a heating rate of 1-2℃ / min and keep it for 5h to obtain Fe2O3 catalyst. Take 1.282g of sodium nitrate and dissolve it in 5mL of deionized water to obtain solution C, disperse the obtained Fe2O3 catalyst in solution C, stir and dry it in a 70℃ water bath, and heat the dried product to 700℃ at a heating rate of 2℃ / min in an NH3 atmosphere and calcine it for 5h to obtain fresh Na / Fe4N.

[0065] Preparation of Pd@MCM-41 catalyst

[0066] Take 6.56g of hexadecyltrimethylammonium bromide and dissolve it in 43mL of water, and mark this solution as solution A. Then, 6.65mL of tetraethyl orthosilicate and 0.27mL of aluminum isopropoxide are dripped into solution A, and this solution is recorded as solution B. 0.36g of palladium nitrate dihydrate is dissolved in 5mL of deionized water, and this solution is recorded as solution C. Solution C is dripped into solution B, and stirred evenly to obtain solution D. Then, 13.6mL of ammonia solution with a mass percentage concentration of 75% is added dropwise to solution D under stirring, and then the mixed solution is stirred at room temperature until a uniform emulsion is formed. The above emulsion is loaded into a hydrothermal reactor, heated to 170℃ for reaction for 36h, and then taken out and naturally cooled to room temperature. Then, the mixture after the hydrothermal reaction is centrifuged, washed to neutrality, dried at 100℃ in a drying oven for 12h, and then calcined in a muffle furnace, heated to 550℃ at 1℃ / min, and calcined for 6h to obtain 3wt% Pd@MCM-41.

[0067] Example 3

[0068] Preparation of Na / Fe4N catalyst

[0069] Take 13.88g of ferric nitrate and dissolve it in 200mL of deionized water to obtain solution A, take another 30.95g of ammonium carbonate and dissolve it in 500mL of deionized water to obtain solution B, add solution B at a rate of 1mL / min until the solution pH reaches 9, continue stirring for 2h and then place it for aging for 10h. The precipitate is washed with 3000mL of deionized water and dried at 90℃ overnight. Grind the dried precipitate and put it into a muffle furnace for calcination, heat it to 500℃ at a heating rate of 2℃ / min and keep it for 5h to obtain Fe2O3 catalyst. Take 0.855g of sodium nitrate and dissolve it in 5mL of deionized water to obtain solution C, disperse the obtained Fe2O3 catalyst in solution C, stir and dry it in a 70℃ water bath, and heat the dried product to 600℃ at a heating rate of 2℃ / min in an NH3 atmosphere and calcine it for 5h to obtain fresh Na / Fe4N.

[0070] Preparation of Pd@MCM-41 catalyst

[0071] Take 4.37g of hexadecyltrimethylammonium bromide and dissolve it in 43mL of water, and mark this solution as solution A. Then, 6.65mL of tetraethyl orthosilicate and 0.27mL of aluminum isopropoxide are dripped into solution A, and this solution is recorded as solution B. 0.12g of palladium nitrate dihydrate is dissolved in 5mL of deionized water, and this solution is recorded as solution C. Solution C is dripped into solution B and stirred evenly to obtain solution D. Then, 13.6mL of ammonia solution with a mass percentage concentration of 75% is added dropwise to solution D under stirring, and then the mixed solution is stirred at room temperature until a uniform emulsion is formed. The above emulsion is loaded into a hydrothermal reactor, heated to 150℃ for reaction for 36h, and then taken out and naturally cooled to room temperature. Then, the mixture after the hydrothermal reaction is centrifuged, washed to neutrality, dried at 100℃ in a drying oven for 12h, and then calcined in a muffle furnace, heated to 550℃ at 1℃ / min, and calcined for 6h to obtain 1wt% Pd@MCM-41.

[0072] Comparative Example

[0073] Preparation of Na / Fe5C2 Catalyst

[0074] Take 10.41g of ferric nitrate and dissolve it in 200mL of deionized water to obtain solution A, take another 23.21g of ammonium carbonate and dissolve it in 500mL of deionized water to obtain solution B, add solution B at a rate of 1mL / min until the solution pH reaches 10, continue stirring for 2h and then place it for aging for 10h. The precipitate is washed with 1000mL of deionized water and dried at 90℃ overnight. Grind the dried precipitate and put it into a muffle furnace for calcination, heat it to 500℃ at a heating rate of 1-2℃ / min and keep it for 4h to obtain Fe2O3 catalyst. Take 0.641g of sodium nitrate and dissolve it in 5mL of deionized water to obtain solution C, disperse the obtained Fe2O3 catalyst in solution C, stir and dry it in a 70℃ water bath, and heat the dried product to 600℃ at a heating rate of 2℃ / min in a CO atmosphere and calcine it for 4h to obtain fresh Na / Fe5C2.

[0075] Preparation of Pd@MCM-41 catalyst

[0076] Preparation steps are the same as Example 1

[0077] Application of Catalyst

[0078] The obtained Na / Fe4N or Na / Fe5C2 catalyst powder and Pd@MCM-41 molecular sieve were respectively tableted at 20 MPa, crushed and sieved to obtain 80-120 mesh particles.

[0079] The CO2 hydrogenation reaction to produce high carbon hydrocarbons is carried out in a fixed bed reaction device. The upper layer of Na / Fe4N or Na / Fe5C2 catalyst particles and the lower layer of Pd@MCM-41 molecular sieve particles are loaded in series in the middle of the reaction tube at a mass ratio of 1:1. The CO2 hydrogenation reaction is carried out at a temperature of 280-360°C, a pressure of 2.0MPa, and an air velocity of 12000h. The volume ratio of CO2:H2 in the raw gas is 1:3. The reaction results are shown in Table 1:

[0080] Table 1

[0081]

[0082]

[0083] Table 1 shows the performance test results of the catalyst example (reaction temperature 330°C, reaction pressure 2.5 MPa, reaction time 20 h, raw gas molar composition: CO2:H2 / Ar=20 / 60 / 20, volume space velocity 12000 h -1 The mass ratio of the upper and lower catalyst layers is 1:1.

[0084] It can be seen from Table 1 that when the mass ratio of the series catalysts is 1:1, the selectivity of the prepared Na / Fe4N high-carbon hydrocarbons is significantly higher than that of the traditional Na / Fe5C2 catalyst. At the same time, when iron nitrate is selected as the iron salt, it has the best high-carbon hydrocarbon selectivity. Then, the mass ratio of the upper and lower catalysts in Example 1 is optimized, and the test results are shown in Table 2.

[0085] Table 2

[0086]

[0087] Table 2 shows the performance test results of the catalyst example (reaction temperature 330°C, reaction pressure 2.5 MPa, reaction time 20 h, raw gas molar composition: CO2:H2 / Ar=20 / 60 / 20, volume space velocity 12000 h -1 )

[0088] It can be seen from Table 2 that when the mass ratio of Na / Fe4N and Pd@MCM-41 is 1:2, it has the highest high-carbon hydrocarbon selectivity.

[0089] Figure 3 Catalytic activity stability diagram of Na / Fe4N+Pd@MCM-41 (reaction pressure 2.5MPa, reaction gas molar composition: CO2:H2 / Ar=20 / 60 / 20, volume space velocity 12000h -1 , the mass ratio of Na / Fe4N and Pd@MCM-41 is 1:2).

[0090] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a tandem catalyst for producing high carbon hydrocarbons by hydrogenation of CO2, characterized in that: The preparation method comprises: Preparation of Na / Fe4N catalyst for preparing light olefins by hydrogenating CO2 loaded on the upper layer of the reactor; and A molecular sieve catalyst for low-carbon olefin polymerization loaded in the lower layer of a reactor is prepared. The molecular sieve catalyst is Pd@MCM-41, which is composed of precious metal Pd embedded in the pores of MCM-41 molecular sieve. The loading amount of Pd is 0.5wt% to 3wt%, and the mass ratio of Na / Fe4N to MCM-41 is 1:4 to 4:

1.

2. The method for preparing a tandem catalyst for preparing high carbon hydrocarbons by hydrogenation of CO2 according to claim 1, wherein the preparation of a Na / Fe4N catalyst for preparing low carbon olefins by hydrogenation of CO2 loaded on the upper layer of a reactor comprises the following steps: S101, adding a metal iron salt to an aqueous solution to form a mixed salt solution, stirring and gradually cooling the solution to 10°C to 30°C, maintaining the constant temperature for 1 to 2 days, and while maintaining the same temperature, dripping an ammonium carbonate solution into the mixed salt solution to form a final precipitation system, wherein the concentration of the metal salt solution is 0.1 to 1.0 mol / L, and the molar amount of ammonium carbonate in the dripped ammonium carbonate solution is 1 to 5 times the molar amount of the metal salt in the mixed salt solution; S102, stirring the final precipitation system for 1 to 10 hours, taking out the precipitate, filtering it, washing it with excess deionized water, drying it, and then calcining it; S103, impregnating the obtained calcined product with 1-10 mL of sodium nitrate solution, wherein the molar amount of sodium nitrate in the sodium nitrate solution is 0.05-0.1 times that of the iron salt; S104, stirring the mixture obtained in step S103 at 80-100° C., evaporating to dryness, and then drying; S105, calcining the product obtained in step S104 under NH3 atmosphere.

3. According to the method for preparing a tandem catalyst for producing high carbon hydrocarbons by hydrogenation of CO2 according to claim 2, the iron salt is a water-soluble divalent or trivalent metal salt, and the iron salt is one of ferrous chloride, ferrous chloride, ferrous nitrate, and ferric nitrate.

4. The method for preparing a tandem catalyst for producing higher carbon hydrocarbons by hydrogenation of CO2 according to claim 2, wherein the dropping speed of the ammonium carbonate solution is 1 to 5 mL / min.

5. According to the method for preparing a tandem catalyst for producing higher carbon hydrocarbons by hydrogenation of CO2 as claimed in claim 2, the temperature range of drying the precipitate in S102 is 80-100°C.

6. The method for preparing a tandem catalyst for producing high carbon hydrocarbons by hydrogenation of CO2 according to claim 2, wherein the calcination temperature in the NH3 atmosphere in step S105 is in the range of 500 to 700°C, and the calcination time is 3 to 5 hours.

7. The method for preparing a tandem catalyst for producing high carbon hydrocarbons by hydrogenation of CO2 according to claim 1, wherein the preparation of a molecular sieve catalyst loaded in the lower layer of a reactor for oligomerization of low carbon olefins comprises the following steps: S201, dissolving a template in deionized water, stirring and dissolving to obtain a clear solution, wherein the template is one or a combination of two or more of hexadecyltrimethylammonium bromide, tetrapropylammonium bromide, n-butylamine, tetraethylammonium hydroxide, tetramethylammonium hydroxide, and tripropylamine; S202, adding the mixed solution of silicon source and aluminum source dropwise into the solution in S201, and stirring thoroughly; S203, dissolving the palladium precursor in a small amount of solvent and dripping it into S202, stirring thoroughly; S204, dropping alkali solution into S203, adjusting the pH value, and obtaining an emulsion; S205, adding the emulsion in S204 into the polytetrafluoroethylene lining to carry out a hydrothermal reaction; S206, washing the mixture after the hydrothermal reaction by centrifugation until it becomes neutral, drying it, and then calcining it in a muffle furnace to remove the template.

8. The method for preparing a tandem catalyst for producing high carbon hydrocarbons by hydrogenation of CO2 according to claim 7, wherein the mass concentration of the template agent can be 3% to 7%; The silicon source is one or a combination of two or more of ethyl orthosilicate, silicic acid and sodium silicate; The aluminum source is one or a combination of two or more of sodium aluminate, aluminum sulfate, boehmite, metallic aluminum, aluminum nitrate, aluminum isopropoxide, and aluminum hydroxide; The palladium salt is one or a combination of two or more of palladium nitrate, palladium chloride and palladium sulfate; The solvent is one or a combination of two or more of water, methanol and ethanol; The alkali solution is one of ammonia water, sodium hydroxide and sodium carbonate, and the adjusted pH value is between 8 and 11; The molar ratio of the silicon source, the aluminum source, the template, the alkali solution and the water in the mixed solution is 1: (0.02-0.05): (0.2-0.3): (4-8): (100-120); The hydrothermal temperature is 1 to 180° C., and the hydrothermal time is 50 to 100 hours; The drying temperature is 80-120°C and the drying time is 4-48h; The calcination temperature is 400-700°C, the heating rate is 0.5-5°C / min, and the calcination time is 8-10h; The particle size of the Na / Fe4N catalyst and the molecular sieve catalyst is 80-120 meshes.

9. A series catalyst for producing high carbon hydrocarbons by hydrogenation of CO2, characterized in that: The tandem catalyst for producing higher carbon hydrocarbons by hydrogenation of CO2 is obtained by the preparation method described in any one of claims 1 to 8.

10. A method for preparing higher carbon hydrocarbons by hydrogenating CO2, characterized in that: The preparation method uses the tandem catalyst obtained by the preparation method according to any one of claims 1 to 8 to prepare high carbon hydrocarbons, and the preparation method comprises: At a reaction temperature of 200-400°C and a reaction pressure of 1.0-3.0 MPa, a mixed gas with a molar ratio of CO2:H2=1:(0.5-5) and a space velocity GHSV of 5000 h -1 ~5000h -1 , react for 50 to 300 hours, collect C at the reactor outlet 5+ Olefin products; CO2:H2=1:(1.0~5.0) CO2:H2 / Ar mixed gas, the volume fraction of Ar in the mixed gas is 30%~60%.

Citation Information

Cited By

  • Preparation and application of modified carbon-supported palladium alloy catalyst with multistage mass transfer channels

    CN120581606A